The future of Japanese diplomacy: Challenges and prospects - Tang, Siew Mun (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2006)
It was not long ago that the US looked upon Japan as a viable challenger to its primacy. Alarmist interpretations of Japan’s ascendancy proved inaccurate, especially after the Japanese economic juggernaut suffered setbacks in the 1990s. The “lost decade” was a period of self-reflection and reform. Concomitantly, Japanese diplomacy was realigned to meet the demands and challenges of the new millennium. This article examines some of the major challenges facing Japan in its efforts to maintain and enhance its international profile. It outlines Japan’s preference for pluralistic leadership, while arguing that Tokyo’s management of its bilateral ties with an ascendant China would play a decisive role in determining Japan’s position in Asia. Additionally, it analyses (a) Japan’s strategic response to North Korea’s saber-rattling, (b) responses to Korean reunification and (c) the issue of Japanese activism. It concludes with a review of issues bearing upon Japan’s future